ANALISIS PENGARUH LIKUIDITAS, PROFITABILITAS DAN LEVERAGE TERHADAP NILAI PERUSAHAAN (Studi Empiris Pada Perusahaan Makanan dan Minuman Yang Terdaftar di Bursa Efek Indonesia Tahun 2018-2021) - Ericke Fridatien; Ahmad Sahri Romadon (ITB AAS Indonesia Surakarta, 2024)
This study aims to examine liquidity, profitability and leverage on firm value. This study used a sample of food and beverage companies listed on the Indonesia Stock Exchange for the 2018-2021 period. This sampling method is using purposive sampling. Based on predetermined criteria, a sample of 28 companies was obtained. This research was conducted with a period of 4 years, bringing the total sample to 112 companies. The type of data used is secondary data taken from the company's financial statements. The analysis technique used in this study is multiple linear regression using the SPSS 26 application program. The results show that liquidity (CR) has no effect on firm value (PBV), while profitability (ROA) has a significant positive effect on firm value (PBV). and leverage (DER) has a significant positive effect on firm value. Keywords: Liquidity, Profitability, Leverage, Firm Value